PROFESSIONAL DEVELOPMENT TRAINING OF THE INTERPRETERS UNDER THE EFFECTIVE INTERCULTURAL COMMUNICATION - Tsaryk, Olha; Rybina, Nataliia; Koshil, Nataliia; Hyryla, Olha (Mountain School of Ukrainian Carpaty, 2021)
The article is devoted to the study of the peculiarities of professional training of interpreters in the framework of intercultural communication. The authors substantiate the expediency of training translation specialists to take into account the correct interpretation not only of specific words and phrases, but also the content of each sentence in the context of the general meaning of the material in the future. The work emphasizes the need to pay attention to the specifics of translation, where there is a difference in the semantic meaning of different cultural terms, and a professionally trained translator in most cases must interpret what is said in another language, avoiding glaring errors, inaccuracies and interpretations in the opposite sense. The authors claim that when considering translation, it becomes important to understand that communication is a kind of interaction between individuals, in which subjects communicating with each other act as subjects of culture, representatives of a certain linguo-socio-cultural community, and translation, being a kind of mediation, is not only a means of interlingual, but also intercultural communication.